Operational Need and Importance of Capacity Management into Hotel Industry – A Review - A.Arun, Ali A. Alalmai , D. Gunaseelan (International Journal of Advanced Science and Technology, 2020)
Hotel industry is a composite of four major operational and many functional departments, the industry needs appropriate management policies to be adopted in all its short-term or long term policies for the smooth running of business. Many micro and macro factors, social or economical have a great influence in creation of demands and needs of the services provided by hotel industry. A well designed capacity management polices into the operational and functional departments required to balance the service provided and the demands of the guest. The study involves in exhibiting a detailed review of capacity management, possibilities in adoption and its need and importance of capacity management in hospitality industry.